2017
DOI: 10.1177/1010428317705131
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk in patients with Peutz–Jeghers syndrome: A retrospective cohort study of 336 cases

Abstract: Peutz-Jeghers syndrome is a rare autosomal dominant inherited disorder characterized by mucocutaneous pigmentation and hamartomatous gastrointestinal polyposis. A growing body of evidence has shown that Peutz-Jeghers syndrome could cause an increased risk of various cancers, yet the range of cancer risk estimates was wide among different studies. In this retrospective cohort study, 336 patients with Peutz-Jeghers syndrome in China were enrolled. The clinical characteristics, cancer spectrum, relative cancer ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
3
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 25 publications
(42 reference statements)
4
36
3
5
Order By: Relevance
“…Additionally, PJS is associated with a high risk of malignancies . Chen et al found that PJS patients were at a high risk of developing colorectal cancer; while among gynecological cancers, the highest relative risk was the development of ovarian cancer . A systematic review showed that the mean age at which PJS developed to cancer was 42 years .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, PJS is associated with a high risk of malignancies . Chen et al found that PJS patients were at a high risk of developing colorectal cancer; while among gynecological cancers, the highest relative risk was the development of ovarian cancer . A systematic review showed that the mean age at which PJS developed to cancer was 42 years .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the high risk of pulmonary cancer, renal cancer, prostatic cancer, bone cancer, and leukemia has also been reported. There is wide variability in cancer risk estimates, as reviewed in a recent meta-analysis study [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The risk for developing cancer at the age of 30, 40, 50 and 60 years is 3-5%, 17-21%, 31-47% and 55-60%, respectively. Gastrointestinal cancer is the most common cancer and the risk is 28-33% at age 60 [21,22]. Because of increased cancer risk in gastrointestinal tract, pancreas, breast and ovary, it has been recommended that patients with PJS be periodically followed to rule out cancers [1][2][3].…”
Section: Discussionmentioning
confidence: 99%